GLOBALIZATION PERIOD PROBLEMS IN THE FAMILY AND THEIR SOLUTIONS - Aminova Manzura Mutalibovna; Muxammadjonova Madina (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In the article, the author, on the basis of factual data, revealed that the causes of the crisis in modern Uzbek families, the increase in family divorce are domestic violence, the oppression of women and their discrimination. In the article, the author identified the reasons that in many cases cause divorce, this is the lack of a woman’s place in the family, as well as the passivity and lack of literacy of a woman who, even those who are subjected to domestic violence, hide and very rarely complain. The facts show that the majority of women, being afraid of the threat of their husbands and because of the reproaches of their parents, according to the mentality of the Uzbeks, divorce is considered a disgrace to the woman’s family, they hide domestic violence. These days, this situation sometimes leads to husbands killing their wives. In the article, the author believes that the reason for this situation is the lack of literacy of women, the early marriage of girls, the choice of husbands by parents and outdated relationships, that is, complete subordination to husbands. In conclusion, the author offers his conclusions and suggestions for eliminating this situation.